2022
DOI: 10.3389/fcell.2022.889972
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 Contributes to the Cholesterol, Glucose, and Insulin2 Homeostasis in Seminiferous Tubules and Maintenance of Immunotolerance in Testis

Abstract: The PCSK9 contribution to cholesterol and immunotolerance homeostasis and response to glucose, and insulin in testis and hypophysis were studied using Pcsk9-deficient (−/−) and transgenic [Tg (PCSK9)] mice, and diabetic, obese ob/ob and db/db mice. The spermatids/spermatozoa acrosome, peritubular vessels, and epididymal adipocytes were PCSK9- and LDL-R-positive. The pro-PCSK9/PCSK9 ratio was high in interstitial tissue-fractions (ITf) and spermatozoa and low in seminiferous tubule-fractions (STf) in normal adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 97 publications
(140 reference statements)
0
0
0
Order By: Relevance
“…Coronary heart disease (CHD) is a prevalent cardiovascular disease and is the leading cause of disability and death in humans [1][2][3]. Over the past half a century, several studies have shown that diabetes, hypertension, dyslipidemia, and smoking are possible risk factors for cardiovascular disease that can be used for the early assessment of the risk for cardiovascular disease [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary heart disease (CHD) is a prevalent cardiovascular disease and is the leading cause of disability and death in humans [1][2][3]. Over the past half a century, several studies have shown that diabetes, hypertension, dyslipidemia, and smoking are possible risk factors for cardiovascular disease that can be used for the early assessment of the risk for cardiovascular disease [4,5].…”
Section: Introductionmentioning
confidence: 99%